The paleoclimatic message from the polymodal grain-size distribution of late Pleistocene-early Holocene Pampean loess (Argentina) - Torre, Gabriela; Gaiero, Diego Marcelo; Cosentino, Nicolas Juan; Coppo, Renata (Aeolian Research)
Wind-blown dust deposits are considered one of the most important terrestrial archives for past climate change studies. In the Southern Hemisphere, the Pampean loess is the most extensive paleo-dust record, whose origin is still a matter of debate. In this paper, grain-size was carried out at three high-resolution loess profiles deposited during the late Pleistocene-early Holocene and for present-day dust collected on the Pampean plain. Based on comparing loess records with in situ present-day dust, this work aims to provide constraints on the climatic conditions that allowed deposition of the Argentinean loess mantle. Unmixing methods allow differentiating three grain-size subpopulations/end members in the Pampean loess which are comparable to end members found in present-day dust. The provenance and transport conditions observed for present-day dust were used to infer that the fine silt components of Pampean loess were transported by high-level air stream associated with the deflation of the Puna-Altiplano Plateau. On the other side, the coarse-silt sediments were carried by dust storms associated with high transport energy events taking place in proximal dust sources. In the central Pampas, the increased abundance of coarse-silt sediments during the Antarctic Cold Reversal (ACR) may indicate the existence of an increased frequency of dust storm episodes. During the beginning of the Holocene, the rise in fine-silt loess could be linked to the activation of distant sources associated with lake desiccation in the Puna-Altiplano Plateau. Fil: Torre, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina Fil: Gaiero, Diego Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de ...